Is It Possible to Combine Non-Invasive Brain Stimulation and Evidence-Based Psychosocial Interventions in Schizophrenia? A Critical Review - Jacopo Lisoni; Gabriele Nibbio; Antonio Baglioni; Simona Dini; Bianca Manera; Alessandra Maccari; Luca Altieri; Irene Calzavara-Pinton; Andrea Zucchetti; Giacomo Deste; Stefano Barlati; Antonio Vita (Brain Sciences)
In schizophrenia, it was suggested that an integrated and multimodal approach, combining pharmacological and non-pharmacological interventions, could improve functional outcomes and clinical features in patients living with schizophrenia (PLWS). Among these alternatives, evidence-based psychosocial interventions (EBPIs) and Non-Invasive Brain Stimulation (NIBS) represent feasible treatment options targeting the clinical features that are unmet needs of PLWS (especially negative and cognitive symptoms). As no clear evidence is available on the combination of these non-pharmacological approaches, this review aimed to collect the available literature on the combination of EBPIs and NIBS in the treatment of PLWS. We demonstrated that the field of combining EBPIs and NIBS in schizophrenia is in its infancy, as only 11 studies were reviewed. In fact, only a few trials, with divergent results, combined these non-pharmacological modalities; while emerging evidence is available on the combination of cognitive remediation and rTMS/iTBS, inconclusive results were obtained. Conversely, albeit preliminary, more solid findings are available on the combination of HF-rTMS and family intervention. Moreover, despite the fact that cognitive activation could not be considered an EBPI, promising results are available in combination with tDCS to improve the working memory domain. To overcome these limitations, we considered several methodological issues to promote research in this field.